Analysis Surface Structure Improvement of Runway Threshold 07-25 Using FAARFIELD - EFENDI, ST., MT, Ir.ACO WAHYUDI (Teknik: Jurnal Ilmu Teknik dan Informatika, 2021)
Runway or runway is an area used by aircraft to take off. The length of the runway depends on the size of the aircraft served. Runway has a pavement structure that can withstand the weight of an aircraft when it wants to fly. This study discusses the damage to the surface structure of the Threshold 07 and Threshold 25 runways at the Sultan Aji Muhammad Sulaiman (SAMS) runway in Sepinggan Balikpapan. Damage to the pavement surface often results from significant heat temperatures from the aircraft when taking off. Visual observations show that there are problems with the Threshold 07 and Threshold 25 pavement surfaces, the damage that occurs is the change in the surface shape of some segments, where the surface deformation eleves are up to 40 mm. Test results from Coredrill samples show that there are internal problems in the asphalt mixture, namely high asphalt content and low density value. By looking at the conditions above, there are problems caused by external and internal factors of the existing pavement, especially the surface conditions namely Threshold which is a location where the load is in MTOW conditions and the aircraft is moving slowly as well as high temperatures (environment and pavement)